2023
DOI: 10.1002/agj2.21342
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid insect protection and fungicide application for managing ear rots and mycotoxins in silage corn

Abstract: Mycotoxins in silage corn (Zea mays L.) accumulate due to ear rot infections by certain ascomycete fungi and cause health issues in livestock. Fungal infections intensify with increase in ear-damaging insect injury and favorable environment in the US Great Lakes region. Therefore, evaluating strategies such as hybrid insect protection and fungicide decisions to manage insects, ear rots, mycotoxin, and silage quality is crucial. Field trials were conducted in randomized complete block design at 11 Michigan site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…In contrast, the effective Vip3A hybrids used in 2018 reduced IFI by >70% across all locations (Table 2). Similar reductions were recently observed by Kaur et al (2023) in silage corn. However, a significant reduction in ear rot and DON in the Vip3A hybrid occurred only at Huron, which had both ideal conditions for fungal infection after silking and significant WBC injury in noneffective hybrid.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, the effective Vip3A hybrids used in 2018 reduced IFI by >70% across all locations (Table 2). Similar reductions were recently observed by Kaur et al (2023) in silage corn. However, a significant reduction in ear rot and DON in the Vip3A hybrid occurred only at Huron, which had both ideal conditions for fungal infection after silking and significant WBC injury in noneffective hybrid.…”
Section: Discussionsupporting
confidence: 89%
“…Smith et al (2018) found that a prothioconazole application at silking in corn did not result in lower ERS compared to a non-treated control. In a recent study in Michigan silage corn, prothioconazole reduced ERI at only two, and DON at four, of 11 site-years (Kaur et al, 2023). Our study reiterates that fungicide applications for ear mold protection in the Great Lakes region are complicated and often have minimal positive return for the grower.…”
Section: Discussionsupporting
confidence: 63%
“…Corn populations and yields in both years were moderate and suitable for good to excellent establishment of interseeded alfalfa treated with PHD followed by FI [3]. Previous work [10,13,[22][23][24] found that directed spray applications of prohexadione on alfalfa and broadcast applications of fungicide and insecticide had little or no impact on corn silage yield. Prior to and 6 weeks following the application of FI, populations of PLH near the research sites were below the economic thresholds set for insecticide treatment of alfalfa over 20 cm in height [25].…”
Section: Weather Conditions Corn Silage Competitiveness and Plh Popul...mentioning
confidence: 88%
“…Both percent ERS and IFS were estimated by counting the total number of damaged kernels on each of the affected ears in a plot divided by the total number of kernels on 10 examined ears in it. All ratings were quantified on a per plot basis (Kaur et al, 2023).…”
Section: Data Collectionmentioning
confidence: 99%
“…The most commonly occurring ear rots in the Great Lakes region are the pink ear rot, caused by Fusarium graminearum (Schwabe [anamorph or asexual stage of Gibberrella zeae Schweinitz Petch]), and the white or Fusarium ear rot, caused by Fusarium verticilloides (Saccardo) Nirenberg (Munkvold, 2003;Sutton, 1982). The injury due to ear-damaging insects can considerably increase the ear rot severity (ERS) due to husk wounds and facilitate infection pathways for fungi (Farhan et al, 2020;Kaur et al, 2023;Singh et al, 2023). Infections by these fungi can also result in the production of mycotoxins (secondary toxic metabolites), which can make silage corn unfit for livestock consumption (Munkvold et al, 2019;Ogunade et al, 2018).…”
mentioning
confidence: 99%